Prognostic Value of 18F-Fluorocholine PET Parameters in Metastatic Castrate-Resistant Prostate Cancer Patients Treated with Docetaxel. (26th March 2019) - Quaquarini, E.; D'Ambrosio, D.; Sottotetti, F.; Gallivanone, F.; Hodolic, M.; Baiardi, P.; Palumbo, R.; Vellani, C.; Canevari, C.; Bernardo, A.; Castiglioni, I.; Porta, C.; et al.
Abstract : Background and Aim . The availability of new treatments for metastatic castrate-resistant prostate cancer (mCRPC) patients increases the need for reliable biomarkers to help clinicians to choose the better sequence strategy. The aim of the present retrospective and observational work is to investigate the prognostic value of 18 F-fluorocholine ( 18 F-FCH) positron emission tomography (PET) parameters in mCRPC. Materials and Methods . Between March 2013 and August 2016, 29 patients with mCRPC were included. They all received three-weekly docetaxel after androgen deprivation therapy, and they underwent 18 F-FCH PET/computed tomography (CT) before and after the therapy. Semi-quantitative indices such as maximum standardized uptake value (SUVmax ), mean standardized uptake value (SUVmean ) with partial volume effect (PVC-SUV) correction, metabolically active tumour volume (MATV), and total lesion activity (TLA) with partial volume effect (PVC-TLA) correction were measured both in pre-treatment and post-treatment 18 F-FCH PET/CT scans for each lesion. Whole-body indices were calculated as sum of values measured for each lesion (SSUVmax, SPVC-SUV, SMATV, and STLA). Progression-free survival (PFS) and overall survival (OS) were considered as clinical endpoints. Univariate and multivariate hazard ratios for whole-body 18 F-FCH PET indices were performed, andp < 0.05 was considered as significant. Results . Cox regression analysis showed a statistically significant correlation between PFS, SMATV, and STLA. No correlations between OS and 18 F-FCH PET parameters were defined probably due to the small sample size. Conclusions . Semi-quantitative indices such as SMATV and STLA at baseline have a prognostic role in patients treated with docetaxel for mCRPC, suggesting a potential role of 18 F-FCH PET/CT imaging in clinical decision-making.